Influence of Use of Non-Inverting Amplifier on Power and Torque - David Yulian; Dwi Sudarno Putra; Martias Martias (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2019)
In the automotive field there are several ways to improve motorcycle performance. One of them can be done through fuel system optimization as outlined in this article. Optimization in this case is to add a non-inverting amplifiers circuit. Based on the results of the study, obtained the maximum average power data when using a non-inverting amplifier is 17.1 HP at 10885 RPM engine speed. Data before using a non-inverting amplifier is only 14.13 HP with 10167 RPM. Power increases by an average of 2.97HP (21.02%). The highest torque when using a non-inverting amplifier is 11.55 N.m. at 7970 RPM engine speed. When not using a non-inverting amplifier, torque is 10.46 N.m at 8112 RPM engine speed. Torque increases at an average of 1.09 N.m (10.42%).